THE ABILITY OF MATHEMATICAL REPRESENTATION AND STUDENT RESPONSE THROUGH PROBLEM-BASED LEARNING MODEL BASED ON MATHMAGIC IN ALGEBRA MATERIAL IN GRADE VII OF JUNIOR HIGH SCHOOL - Sintya Masliyani; Ahmad Yani T; Dede Suratman (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2025)
The purpose of this research is to demonstrate the mathematical representation abilities between students who participate in learning using a mathmagic-based problem-based learning model and the mathematical representation abilities of students who use the conventional lecture method. The research subjects involved 36 students from SMP Negeri 4 Sungai Raya, consisting of class VII B as the control class and class VII F as the experimental class. The research method used is quantitative, with instruments in the form of short answer questions packaged in a math magic format. The data was analyzed using normality tests, homogeneity tests, and hypothesis testing through independent sample t-Test and Pearson Product Moment correlation tests. The results of the study indicate that the problem-based learning model based on mathmagic is more effective in enhancing mathematical representation skills compared to the conventional lecture method, with a significance value of 0.035 indicating a difference in average ability between the two classes. In addition, the results of the Pearson correlation test showed an r value of 0.228, indicating a positive relationship between students' mathematical representation skills and their responses, where students with higher representation skills tend to provide positive responses.